Overcoming Challenges in P5 Implementation : Teachers’ Strategies for Digital Native Students - Irsandhi, Marcel Muhammad; Yunazar, Rizky; Astutik, Dwi (Universitas Pendidikan Mandalika, 2025)
The study aims to explore the strategies used by teachers in responding to students from the digital native generation in the implementation of the P5 program in schools. This study uses a qualitative approach with a case study method. The data collection techniques in this research utilize interviews and observations. The research was conducted at SMA Batik 1 Surakarta, one of the schools implementing a technology and digitalization-based P5 program. Data analysis in this study uses the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The findings of this study show that teachers have strategies such as providing flexibility in accessing technology but still require direct supervision from the teachers. In addition, teachers also provide opportunities for students to present their work through exhibitions of their creations, so students must understand their work and refrain from dishonesty in the use of technology.